DUI recidivism by intervention adherence: a multiple risk factor approach. (2nd September 2016) - Robertson, Angela; Gardner, Sheena; Walker, Courtney S.; Tatch, Andrew
ABSTRACT: Background : Multi-component impaired driving interventions can reduce driving under the influence (DUI) recidivism rates; however, outcomes are better for those who complete the interventions and are adherent with program expectations. Research is needed to examine the differences between DUI offenders who are adherent vs. non-adherent to intervention efforts. Objective : The current study utilized a multi-risk factor model to predict recidivism among first-time DUI offenders enrolled in an intervention program. Differences between offenders who were adherent (including program completion) vs. non-adherent with the intervention were examined. Method : Using data from the Mississippi Alcohol Safety Education Program (MASEP) and state administrative records, the current study examined both recidivism rates and rates of intervention completion for all individuals enrolled in the program. The sample was predominantly White (58.8%) and male (80.2%). Results : Individuals who were adherent with the intervention were significantly less likely to recidivate within 3 years. Prior traffic or other criminal violations positively predicted recidivism rates. The likelihood of recidivism varied, with males, African Americans, and younger individuals with less education at greater risk of recidivism. Adherence with the intervention was more common for African American and older participants. Conclusion : The MASEP participants who were adherent with the intervention were significantly less likely to recidivate than those who were non-adherent. However, variance in the multi-component intervention completion rates suggests that the program resonates better with specific population subsets. We argue for researchers and policymakers to further explore how specific population subsets react to varying intervention programs to maximize efforts to reduce impaired driving.